Endocannabinoid and N-acylethanolamine concentrations in hair of female patients with posttraumatic stress disorder – associations with clinical symptoms and outcomes following multimodal trauma-focused inpatient treatment - L. Bergunde; M. L. Woud; L. Shkreli; L. Schindler-Gmelch; S. Garthus-Niegel; S. E. Blackwell; C. Kirschbaum; H. Kessler; S. Steudte-Schmiedgen (Translational Psychiatry)
Abstract While psychotherapeutic treatments for posttraumatic stress disorder (PTSD) show in general good responses in affected individuals, 30–40% of patients show limited improvement. On a biological level, the endocannabinoid system of the body may play a role in the aftermath of trauma, in PTSD, and in extinction processes. This study is a secondary analysis of a randomized-controlled trial including patients with PTSD over the course of trauma-focused inpatient treatment. It aimed to investigate whether endocannabinoid system alterations are associated with symptom severity and treatment response. Fifty-four female inpatients with PTSD provided hair samples and completed psychometric questionnaires at pre-treatment, post-treatment, and 3-month follow-up. Endocannabinoid (EC: AEA, 1-AG/2-AG) and N-acylethanolamine (NAE: SEA, PEA, OEA) concentrations were measured in scalp-near 3-cm hair segments, reflecting cumulative concentrations in the 3 months prior to sampling. At pre-treatment, higher depressive and anxiety symptoms were significantly associated with lower hair AEA levels, whereas higher PTSD symptoms (when controlling for depressive symptoms) and more traumatic experiences were significantly associated with higher hair AEA and NAE levels respectively. PTSD symptoms improved across treatment, remaining stable at 3-month follow-up, but were predicted neither by pre-treatment hair ECs/NAEs nor their changes across treatment and follow-up, which was confirmed in subgroup analyses. Our findings suggest that hair ECs/NAEs may be distinctly linked with trauma-related and affective and anxiety symptoms, however, do not predict treatment response in PTSD. This challenges expectations and highlights the complexity of endocannabinoid system alterations in stress-related psychopathology. Given the study’s limitations, including a female-only sample and lack of a control group, larger studies with control groups and multiple biomarkers are needed to identify intervention-related biomarkers in PTSD.